CONSERVATIVE VERSUS OPEN REDUCTION INTERNAL FIXATION (ORIF) FOR PEDIATRIC SUPRACONDYLAR HUMERUS FRACTURES GARTLAND TYPE II AND III: A SYSTEMATIC REVIEW - Gunawan, Indra (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Displaced supracondylar humerus fractures in pediatric patients constitute a challenge for surgeons, since the optimal treatment remains debatable in terms of functional and cosmetic outcomes as well as surgical risks. Aim: The objective of this study is to compare the outcomes of conservative versus Open Reduction with Internal Fixation (ORIF) for pediatric supracondylar humerus fractures gartland type II and III. Methods: A systematic review was conducted using PubMed and Google Scholar in accordance with the PRISMA guidelines. Studies comparing conservative versus ORIF surgery for Supracondylar Humerus Fractures Gartland Type II and III, with Flynn criteria as the primary outcome, were considered eligible. Excluded were studies of only one surgical procedure modality, Gartland type I, as well as case reports. Results: A total of 128 patients aged 1–15 years old were included in the analysis. Study designs were all cohort prospective (Level II-III). From 128 patients, 69 patients were treated conservatively and 59 operatively by ORIF. From 69 conservatively treated patients, most were Gartland type II whereas in the ORIF group, most were Gartland type III. Based on Flynn’s Criteria, satisfactory outcomes (excellent or good) were achieved in the majority of patients in the conservative and in the ORIF group. However compare to conservative treatment, ORIF have higher rates of satisfactory functional outcome. Conclusion: ORIF delivers superior functional and cosmetic outcomes when compared to conservative treatment for pediatric supracondylar humerus fractures.